The Evaluation of Teaching Methods and Training in Zakho University Based On Participant’s Views - Haji, Satar J.; Suliman, Mohammed I. (Humanities Journal of University of Zakho, 2015)
The aim of the research is to evaluate the teaching methods and the academic training according to the points of view of the trainers, and to realize that, the two researchers select two goals for the research which are: 1- Recognize the trainers opinions towards the course of teaching methods and Academic training. 2- Revealing the comparison among the opinions of the trainers according to the Variable (gender, specialization) The sample of the research involved (27) teachers of Zakho university who participated in the course of teaching methods which submitted in the mentioned university (2013 - 2014).The two researchers depended on the descriptive and analytic procedure to describe the symptom as it is in the real evidence, the two researchers prepared a questionnaire to measure that in (28) sections distributed in five fields (evaluation of the lecturer, the scientific subject, the regulation field, the results of the course).After the end of the course period, the two researchers implemented the tool on the individuals of the sample of research and collected the data, as well as, analyzed it statistically by using of the suitable statistic means and statistic program (spss) , the results were appeared as the following points: 1- There is an indicate comparison in the opinions of the trainers in favor of the Course program. 2- There is an obvious comparison between the intermediate opinions of the trainer according to variable (gender) and it was in favor of males. 3- There is no comparison between the intermediate opinions of the trainers in Accordance with variable (specialization).